O uso de tu/você em cartas baianas pessoais do século XX em relações de simetria - Batista, Priscila Starline Estrela Tuy (2017)
This paper analyzes the use of the forms tu and você in the position of full subject, in personal letters written by poorly and moderately schooled Bahians between the 1930s and 1980s, in more intimate and less intimate contexts (family, close friends, and boyfriends). It was sought to raise the communicative situations in which tu and você were produced, in order to identify the factors that possibly influenced the use of such forms. Also, the senders were distributed by the subsystems proposed by Lopes and Cavalcante (2011) to control the behavior of each sender and to identify the most productive subsystem in the sample of missives analyzed. We also present a contrastive study with the Brazilian states of Rio de Janeiro and Minas Gerais. The material analyzed refers to 70 letters, unpublished, that are part of the collection of the Estrela Tuy Family (1930-1980). Regarding the data, after the manual collection, the data search tool E-Corp was used to ensure the accuracy of the data collected. Afterwards, the data was analyzed according to the principles of Quantitative Sociolinguistics (LABOV, 1994), with the support of the Goldvarb X software, also considering Brown and Levinson's Theory of Polity (1987) to identify the types of relationships established between senders and recipients, in order to take into account the preservation of the face between the interactants. Regarding the results, they indicate the majority use of você in the epistolary documentation in question, in contexts of greater and lesser intimacy, and the use of tu, only in the letters of greater intimacy. In this way, it is understood that in the sample of analyzed letters, the use of você is quite generalized, whereas the tu was not very productive.